The Practice of Online Teaching at Shanghai International Studies University during the COVID-19 Pandemic - Zhang, Yanli; Yang, Zihua; Chen, Yongtao (Journal of International Students, 2022)
We examined the practice of online teaching at the School of Chinese Studies and Exchange, Shanghai International Studies University during the Covid-19 pandemic, with both qualitative and quantitative research methods. Based on the analysis, the importance of incorporating web-based teaching into international students’ education is discussed. Suggestions are then given from six different perspectives about further developing undergraduate education for international students in the post-pandemic period.